Classificados do jornal Folha de S. Paulo: os sentidos de um rato no discurso publicitário - Souza, Beatriz Tavares de (2009)
The changes in advertisement speech that goes around in the media is the result that is coming from the social capitalism behavior which has a dynamic consumism. So, the purpose of this research is to investigate the language mechanism which Folha of São Paulo Brazilian Newspaper has all the classified advertisement. The objective is to understand how to build the ethos in enunciation and by enunciation showing as a suitable relation established between enunciator Folha of São Paulo newspaper and co-enunciator reader/consumer, as such setting speech. This scenery was created and developed around the mouse cartoon, protagonist, who is the advertisement boy of Folha of São Paulo classified advertisement who image was changed from time to time by constantly modification specially involving in a inter-speech approach originating from several fields. The theoric perspective based on speech studies, the linguistic structure applied speech and work, linked to research group Atelier speech study that dispatch to language activity in differents contexts that my research look for abstract from advertisement the inter-relation speech showed by the newspaper using a mouse cartoon. . By the material collection to be analyzed, classified advertisement of Folha newspaper, that includes verbal texts and drawn images, turning to an specific discursive speech verb-visual, postulating the theories of the speech analysis on spilling enunciative formulated by Maingueneau (2005a and 2005b) mainly guiding the analytic activity by conception of interdiscursive practice, proposed by this author, that says domain texts in a same field must be interpret using the same semantics level. The methodology will use data that has been already collected; delimit of corpus for analysis; category establishment, analysis strictly speaking